Implementasi Algoritma Rule-Based dalam Penentuan Tata Letak Sanggah Merajan - Ni Kadek Rika Dwi Utami; I Wayan Supriana (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2025)
Balinese traditional architecture holds deep philosophical and spatial meanings, particularly in the design of sacred family shrines known as merajan. However, the complexity of applying Asta Kosala Kosali principles often poses challenges, especially for the younger generation unfamiliar with traditional spatial knowledge. This research aims to develop a web-based simulator that assists users in designing merajan layouts by implementing a rule-based algorithm derived from literature and expert interviews. The simulator processes user inputs such as land dimensions and traditional measurement units to generate an automated visual layout that aligns with cultural rules. The methodology includes knowledge acquisition, rule formulation, system architecture design, and functional implementation. Functional testing confirms that the system can accurately position sacred structures according to the Sanga Mandala zoning concept and calculate distances based on customary units like alengkat and limang nyari. Usability testing involving 38 respondents using the System Usability Scale (SUS) method results in a high usability rating, indicating the system’s ease of use and usefulness. This research contributes to the digital preservation and dissemination of Balinese spatial wisdom and provides a foundation for future development of interactive cultural heritage tools.